Question
\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Find: } f \circ g(x) \]
Ask by Warren Welch. in Tanzania
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( f \circ g(x) = 6x - 5 \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Bonus Knowledge
To find \( f \circ g(x) \), we need to substitute \( g(x) \) into \( f(x) \). First, calculate \( g(x) \): \[ g(x) = 2x - 3 \] Now substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(2x - 3) \] Now, plug \( 2x - 3 \) into the function \( f(x) \): \[ f(2x - 3) = 3(2x - 3) + 4 \] Distributing the 3 gives: \[ = 6x - 9 + 4 \] Combining like terms: \[ = 6x - 5 \] So, \( f \circ g(x) = 6x - 5 \).